Studi Hasil Pemeriksaan Protein Urin Segera pada Pasien Infeksi Saluran Kemih menggunakan Asam Sulfosalisilat di RSU Wisata Universitas Indonesia Timur - Rifkatul Mukarramah; Nardin Nardin; Nurul Utami (Jurnal Media Laboran, 2018)
Urine comes from blood that has been filtrated by the glomerulus and then secreted, absorpted and excreted through the urinary tract. The urine protein test aims to determine the results of immediate urine protein examination in patients with urinary tract infections using 40% and 60% sulfosalicylic acid. The research was carried out in all experiments which aimed to determine the results of immediate urine examination using sulfosalisial acid 40% and 60% with sampling techniques carried out by purposive sampling. Based on the results of the research that has been done, it shows that there is no significant difference using sulfosalicylic acid 40% and 60%. Based on the results of the above research, it is suggested that the concentration of sulfosalicylic acid 40% and 60% can be used during the examination of urine protein, but in the examination of urine, the urine sample that is well examined is a urine sample immediately because the urine that has been left behind for a long time can affect the examination results.